GURU AGAMA KRISTEN SEBAGAI PENDIDIK DAN AGEN TRANSFORMATION LEADERSHIP SERTA RELEVANSINYA BAGI LEMBAGA PENDIDIKAN KRISTEN - Jesy Fieny Mangopo; Neli Seba, Hansdeni R., Jepri Bassi, Tri Kusuma Ati (CV. ADIBA ASIHA AMIRA, 2025)
Transformational leadership is a dynamic approach in directing a group or organization, focusing on efforts to motivate and inspire team members to achieve their utmost potential. Through an inspiring vision, innovative thinking, individual attention, and integrity as an example, this leadership style strives not only to achieve business goals but also to positively transform organizational culture. By linking personal and organizational objectives, transformational leadership becomes a catalyst for change that drives collective growth and individual development in the workplace. It not only drives changes in performance and productivity but also concentrates on fostering interpersonal relationships and cultivating leadership potential within the team. By providing inspirational impetus, sparking critical thinking, recognizing individual needs, and demonstrating trust and integrity, transformational leaders create an environment that supports the exploration of new ideas and collaboration. Furthermore, this leadership approach has a lasting impact on developing individuals with strong work ethics, integrity, and the ability to lead by example, which in turn can shape an inclusive and innovative corporate culture. Through an approach that focuses on individual and collective transformation and teaching that is inspirational, faith- based role modeling, and the cultivation of social skills based on Christian principles, they create an inclusive and spiritual learning environment, shaping a brighter future for the organization and its team members